Feasibility Study of Charging Infrastructure to Increase Vehicle Electrification in Indonesia - Hanun, Ilza Athiyatamimy; Sutopo, Wahyudi; Rochani, Renny (Jurnal Teknik Industri: Jurnal Keilmuan dan Aplikasi Teknik Industri, 2023)
Progress in developing electric vehicles (EVs) has resulted in substantial advancements in recent years. EVs can effectively reduce carbon emissions while allowing vehicle manufacturers to build a strong presence in emerging markets. Nevertheless, the rapid growth of EVs in Indonesia requires more significant expansion. The lack of sufficient facilities to cope with the demand for EVs has led to customer reluctance to adopt this mode of transportation. Also, there is a notable hesitancy among manufacturers and business professionals to engage in the production of EVs and the establishment of charging infrastructure. This hesitation arises primarily from the lack of apparent market demand, which may be attributed to the significant investment costs associated with these ventures. This study, therefore, aims to develop an Annual Cost of the System (ACS) cost model to assess and select potential economically feasible and operationally feasible investments for the provision of Public Electric Vehicle Charging Stations (SPKLU) and Public Electric Vehicle Battery Exchange Stations (SPBKLU) services in Indonesia. When creating investment decisions, it is necessary to take into consideration a range of feasibility analysis variables, including but not limited to Net Present Value (NPV), Internal Rate of Return (IRR), and Payback Period (PBP). Moreover, this study additionally performed a sensitivity analysis to determine actionable recommendations for individuals within the business community.